2011
DOI: 10.1016/j.drugalcdep.2011.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in pharmacokinetics of maintenance dosed buprenorphine

Abstract: Aims Gender differences are known to occur in the pharmacokinetics of many drugs. Mechanisms may include differences in body composition, body weight, cardiac output, hormonal status, and use of different co-medications. Recently subtle gender-dependent differences in cytochrome P450 (CYP) 3A-dependent metabolism have been demonstrated. Buprenorphine N-dealkylation to norbuprenorphine is primarily performed by CYP3A. We therefore asked whether gender-dependent differences occur in the pharmacokinetics of bupre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Interestingly, corroborative evidence has been reported in a recent study, where buprenorphine has been shown to inhibit the glucuronidation of norbuprenorphine, the only clearance pathway for norbuprenorphine, in multiple in vitro systems [8]. The results of this recent study assumes greater importance since 3-norbuprenorphine glucuronide was found to be a major circulatory species with five-to 13-fold higher levels as compared to 3-buprenorphine glucuronide in several clinical studies following buprenorphine dosing [9,10].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, corroborative evidence has been reported in a recent study, where buprenorphine has been shown to inhibit the glucuronidation of norbuprenorphine, the only clearance pathway for norbuprenorphine, in multiple in vitro systems [8]. The results of this recent study assumes greater importance since 3-norbuprenorphine glucuronide was found to be a major circulatory species with five-to 13-fold higher levels as compared to 3-buprenorphine glucuronide in several clinical studies following buprenorphine dosing [9,10].…”
supporting
confidence: 86%
“…Interestingly, although the formation of nurbuprenorphine suggests a clear route dependency, as evidenced by the norbuprenorphine/buprenorphine exposure ratios following transdermal (average 0.32), sublingual (average 1.52) and intravenous (average 0.19) drug administration of buprenorphine [4,9,11], the involvement of the glucuronidation pathway for the clearance of norbuprenorphine is highly inevitable regardless of the route of administration. Hence, the qualitative evidence gathered by the cursory data analysis in this report needs further probing because increased circulatory levels of norbuprenorphine in the elderly may contribute to several safety issues, including respiratory depression.…”
mentioning
confidence: 99%
“…The metabolic ratios of 7-hydroxyl-veratramine and veratramine-3-O-sulfate calculated in plasma were 27.8 ± 4.8% and 33.7 ± 16.7%, respectively, in male rats compared with 3.4 ± 1.2% and 93.8 ± 1.8% in female rats, which indicated distinct gender differences. Mechanisms of gender-dependent pharmacokinetics may include differences in cardiac output, body composition, body weight, hormonal status, and metabolism between genders (57,58). One factor commonly known to contribute to gender-related metabolism, the major reason for gender difference on pharmacokinetic behavior, is the differential expression of drug-processing enzymes including phase I and phase II metabolic enzymes (P450s, sulfotransferases, glutathione transferases, and UDP-glucuronosyltransferases) (59).…”
Section: Discussionmentioning
confidence: 99%
“…Women, for example, have a higher AUC of buprenorphine than men, possibly due to differences in body composition, as well as potential differences in CYP 3A4 [27]. …”
Section: Overview Of Drug Dispositionmentioning
confidence: 99%